Research Trends on Cobalt-Doped Hydroxyapatite: Bibliometric Analysis and Emerging Applications: Research Trends on Cobalt-Doped Hydroxyapatite: Bibliometric Analysis and Emerging Applications - Ahmad, Zeeshan; Nisa, Mehru; Fatimah, Is (Chemistry Department, Universitas Islam Indonesia, 2026)
This bibliometric review is a 98-article (2015-2025) review of cobalt-doped hydroxyapatite (Co-HAP) that emphasizes the trends in catalysis, biomedicine, and environmental remediation. The study is based on Scopus data and bibliometric tools to find out the key research findings, the most active contributors, and the most popular journals. Commonly reported methods of characterization include XRD and SEM. The results highlight the growing global cooperation and the continuous growth in publications, which indicates the continued presence of innovation and interdisciplinary applicability of Co-HAP studies.